Sphaerosporella brunnea (Alb. et Schwein.) Svrcek et Kubicka, un discomicete con incidencia en la truficultura e interés forestal - García-Montero, L. G.; Galán Márquez, Ricardo; Di Massimo, G.; García Manjón, José Luis; Díez, J. (Revista Catalana de Micologia, 2007)
Sphaerosporella brunnea (Alb. et Schwein.) Svrcek et Kubicka, a cup-shaped ascomycete related with truffle cultures and afforestation. A casual finding of Sphaerosporella brunnea in some greenhouses from Spain, growing in connection with several ectomycorrhizal plants, is reported. These plants were experimentally inoculated with low level inoculum of Tuber melanosporum. Sphaerosporella brunnea is described and illustrated, and its negative role in truffle cultures and its possible utilization in burned are as recovery is emphasized.